Imperial Russian rule in the Kingdom of Poland, 1864-1915 - Rolf, Malte (Russian and East European studies., 2021)
"After crushing the Polish Uprising in 1863-1864, Russia established a new system of administration and control. Imperial Russian Rule in the Kingdom of Poland, 1864-1915 investigates in detail the imperial bureaucracy's highly variable relationship with Polish society over the next half century. It portrays the personnel and policies of Russian domination and describes the numerous layers of conflict and cooperation between the Tsarist officialdom and the local population. Presenting case studies of both modes of conflict and cooperation, Malte Rolf replaces the old, unambiguous "freedom-loving Poles vs. oppressive Russians" narrative with a more nuanced account and does justice to the complexity and diversity of encounters among Poles, Jews, and Russians in this contested geopolitical space. At the same time, he highlights the process of "provincializing the center," the process by which the erosion of imperial rule in the Polish Kingdom facilitated the demise of the Romanov dynasty itself"--